Philosophical Values and Local Wisdom in Java Panggih Traditional Ceremony Language - Indrati, Septin Lovenia (Master Program in Linguistics, Diponegoro University, 2017)
Traditional ceremony is currently displaced by the development of the times and technological advances. Society in general no longer understand the value of philosophy and local wisdom in traditional ceremonies. One of the traditional ceremonies that is currently faded is a traditional ceremony of calling. In this paper will be discussed how the value of philosophy and local wisdom Javanese traditional ceremonies is represented. The data were taken from the wedding ceremony especially the panggih session. They were taken using observation and analyzed with referential technique. The result shows that in panggih, we can find some philosophical values and local wisdom like in marriage, the couple must have good relationship and communication, and are equal. They have responsibilities and love each other. The local wisdom contained in the panggih ceremony is balangan gantal sirih, wijik dadi, kacar-kucur or tampa kaya, dhahar klimah, and sungkeman